Confluent cavitated nodules in invasive mucinous adenocarcinoma: A case report. Issue 4 (2023) - López-Hinostroza, Madaleine; Dávila, Juan; Asencio, Angélica Y.; Moya-Salazar, Jeel
No abstract available